Kosmopolitanisme dalam Novel "Kapas-Kapas Di Langit" Karya Pipiet Senja: Analisis Sosiologi Sastra - Supiyatna Supiyatna; Sumaryoto Sumaryoto; Mamiek Suendarti (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2022)
The purpose of this study is to show the cosmopolitan behavior of the characters in the novel Kapas-Kapas Di Langit by Pipiet Senja based on a review of the sociology of literature and its implementation for literary learning in SMA/MA.  This research is qualitative, with a descriptive method, and uses content analysis techniques on a primary data to be studied.  The data that becomes the object of research is a novel entitled Kapas-Kapas Di Langit by Pipiet Senja.  The results of the discussion found an analysis of 7 (seven) cosmopolitan identities as many as 26 findings, including (a) global or local hybridization that has common interests as many as 3 analysis findings, (b) competence (intercultural) in respecting local cultural diversity as much as 2 analysis findings.  , (c) willingness and openness to involve themselves in cultural diversity as many as 6 analysis findings, (d) mobility to travel as much as 1 analysis finding, (e) refusing the "tourist" type approach as many as 4 analysis findings, (  f) desire to be able to feel variations in citizenship and postmodern as many as 4 analysis findings, and (g) critical attitude towards their own nation and country of origin as many as 6 analysis findings. Keywords: Cosmopolitan, novel, sociology of literature.